Integration, demands and accommodations: An exploration of summative assessment practices in Dutch bilingual secondary education: An exploration of current practices - Mearns, Tessa; van Beuningen, Catherine; Nederlof, Niels; de Jong, Nivja (Dutch Journal of Applied Linguistics, 2025)
In content and language integrated learning (CLIL), the goal is to support learning of both subject content and (subject-related) language, through an integrated approach. Based on the principle of constructive alignment (Biggs, 1996), it is logical to assume that such integration carries through to assessment. This study explores the extent to which this is the case in the context of bilingual secondary education in the Netherlands. Drawing on quantitative, self-report data from a teacher questionnaire, and qualitative analysis of assessment materials, we explore the relative roles of language and content, the use of accommodations and translanguaging as support, and the cognitive and linguistic demands posed by assessments. In line with previous research, it appears that assessment practices do not always align with the integrated goals of CLIL. Implications for practice are discussed, as is the need for more attention for this aspect of CLIL in research and teacher education.